Early Childhood Value and Character Construction through Great Child Habituation Content on social media: An Analysis of Adaptive Parenting Modelling Practices and Design - Alfi Rohmatul Azizah; Alif Mudiono; Eny Nur Aisyah (Ittishal Educational Research Journal, 2026)
The present study has been developed for the purpose of analyzing the process of establishing early childhood values and characteristics in the context of "Great Child Habituation." A central objective of this study is to examine the way routines are represented in the formation of character. In addition, the study will serve to formulate technology-based adaptive parenting models. The research employs a qualitative approach, utilizing content analysis of videos on TikTok and Instagram. The data undergoes multimodal analysis, encompassing visual, auditory, and textual dimensions, to discern patterns in the construction of character value. The results of the study demonstrate that character values, such as discipline, independence, responsibility, religiosity, and empathy, are constructed through concrete, repetitive, and reinforced routines, as well as narratives and symbolic framing. Routine representation serves as the primary mechanism of character internalization through consistent habituation. Furthermore, this research produces a technology-based adaptive parenting model that places digital content as a stimulus, parents as active mediators, and routines as a bridge in the formation of children's characters.